Determination of heart rate threshold from heart rate kinetics during maximal graded exercise in soccer players - Silvio Rodrigues Marques Neto; Alexandre Gurgel; Eduardo Lattari; Viviane Faleiro; Sérgio Machado; Paulo Farinatti; Geraldo Maranhão Neto (Universidade Federal de Santa Catarina, 2019)
The main of the present study was to identify the heart rate threshold based on heart rate kinetics during graded maximal exercise in football players. Twenty-six male football players performed a maximal exercise test (Bruce protocol) on a motor-driven treadmill. Oxygen uptake (VO2) and heart rate (HR) were monitored, recorded and resampled at 3.5Hz. The ventilatory threshold (VT), and respiratory compensation (RC), heart rate deflection points (HRDP1 and HRDP2) and heart rate kinetics threshold (HRT) were determined by computerized methods. The heart rate variability (HRV) was assessed in the frequency domain. The HRT averaged 89.9 ± 1.2 % of the VO2 peak. The HRT showed poor correlations and significant differences compared with HRDP1 (r = 0.46) and VT (r = 0.51), but was not different from, and highly correlated with, HRDP2 (0.98) and RC (0.90). Bland Altman plots showed all athletes into 95% of limits of agreement, and intraclass correlation coefficient showed good agreements between points obtained from HRT compared with HRDP2 (0.96) and RC (0.98). The HRT was highly correlated with HRDP2 and RC, suggesting it could be a marker for cardiorespiratory fatigue.